2020
DOI: 10.1093/rheumatology/keaa028
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound verified enthesophytes are associated with radiographic progression at entheses in psoriatic arthritis

Abstract: Objectives The aim of this prospective study was to examine whether ultrasound or clinical abnormalities at enthesal sites predict radiographic progression at entheses in psoriatic arthritis (PsA). Methods Consecutive PsA patients were included and subjected to clinical and ultrasound assessments at 14 entheses at baseline, 6 and 12 months. Radiographs were performed at 0 and 12 months. By US, we investigated structural (eros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Analysis of total PASI revealed that the total PASI scores of the two groups after treatment were significantly lower than those before treatment, and the total PASI score of the observation group after treatment were lower than those of the control group, and the difference had statistical significance ( P < 0.05). Such results were similar to the study by Lackner et al [ 27 ], indicating that the improvement effect of ephedra-forsythia-red bean decoction addition and subtraction in the treatment of psoriasis vulgaris was better than that of the control group. Further comparison of the efficacy indicators showed that the overall response rate (87.5%) in the observation group was significantly higher than that in the control group (67.5%), and the difference had statistical significance ( P < 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Analysis of total PASI revealed that the total PASI scores of the two groups after treatment were significantly lower than those before treatment, and the total PASI score of the observation group after treatment were lower than those of the control group, and the difference had statistical significance ( P < 0.05). Such results were similar to the study by Lackner et al [ 27 ], indicating that the improvement effect of ephedra-forsythia-red bean decoction addition and subtraction in the treatment of psoriasis vulgaris was better than that of the control group. Further comparison of the efficacy indicators showed that the overall response rate (87.5%) in the observation group was significantly higher than that in the control group (67.5%), and the difference had statistical significance ( P < 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies in SpA and PsA demonstrated that ultrasound verified enthesitis does not correlate with clinical signs of enthesitis (20). We previously observed that enthesophytes but neither PD nor clinical tenderness at entheses were linked with radiographic enthesal progression (32). Whether similar result could be found in SpA and whether clinically quiescent but sonographically active enthesitis would predict future clinical worsening are questions that only future research can clarify.…”
Section: Discussionmentioning
confidence: 87%
“…The prevalence of syndesmophytes was higher in patients with than in those without US evidence of enthesophytes (26% vs 6%) [54]. Furthermore, a very recent study by Lackner et al reported that US baseline enthesophytes at the MASEI entheseal sites were predictive of radiographic progression at entheseal level after 12 months in a cohort of 43 PsA patients [55].…”
Section: Sonographic Enthesitis and Psoriatic Arthritis Severitymentioning
confidence: 97%
“…Furthermore, a very recent study by Lackner et al reported that US baseline enthesophytes at the MASEI entheseal sites were predictive of radiographic progression at entheseal level after 12 months in a cohort of 43 PsA patients [ 55 ].…”
Section: Sonographic Enthesitis and Psoriatic Arthritis Severitymentioning
confidence: 99%
See 1 more Smart Citation